The Effect of Personal Selling and Ease of Claim Settlement on the Increasing Number of Customers at PT. Jasindo Sharia Insurance Banjarmasin - Riswan Yunida; Linda Permanasari; Muhammad Wahyu Wardhana; Novi Shintia; Hairul Anwar (Cita Konsultindo Research Center, 2023)
The research objectives are (1) To find out Personal Selling and Ease of Claim Settlement have a simultaneous effect on increasing the number of customers at PT. Jasindo Sharia Insurance Banjarmasin, (2) To find out Personal Selling and Ease of Claim Settlement have a partial effect on increasing the number of customers at PT. Jasindo Sharia Insurance Banjarmasin and (3) To find out the variables of Personal Selling and Ease of Claim Settlement which are the most dominant in influencing the increase in the number of customers at PT. Jasindo Sharia Insurance Banjarmasin. This research method is a quantitative study using a sampling technique for 100 customers of PT. Jasindo Sharia Insurance Banjarmasin as respondents. The data analysis technique uses multiple linear regression analysis techniques. The results of the study show that: (1) The independent variables; Personal Selling (X1) and Ease of Claim Settlement (X2) simultaneously affect the variable Increase in the Number of Customers (Y) by 24.6% and the remaining 75.4% is influenced by other variables in outside of this research. (2) Personal Selling Variable (X1) has a partial significant effect on the increase in the number of customers (Y) with a tcount of 3.577. (3) The Ease of Claim Settlement Variable (X2) has a partial significant effect on the Increase in the Number of Customers (Y) with a tcount of 1,968. (4) The Personal Selling variable has the most dominant influence on the increase in the number of customers (Y) with an r2 value of 0.116 or 11.6%.